Relationship Between the President and the DPD in Indonesia’s Asymmetric Bicameral System - Irmanjaya Thaher; Markoni Markoni; Dzaki M. Ihsan (Hakamain: Journal of Sharia and Law Studies, 2024)
This study examines the constitutional relationship between the President and the Regional Representative Council (Dewan Perwakilan Daerah/DPD) within Indonesia’s asymmetric bicameral system, focusing on how institutional design influences executive-legislative relations and regional representation. Although the 1945 Constitution recognizes the DPD as the second chamber of parliament, its legislative, supervisory, and advisory powers remain significantly weaker than those of the House of Representatives (Dewan Perwakilan Rakyat/DPR), creating an imbalance that limits its constitutional role in overseeing executive policies affecting regional interests. This research employs a normative legal method based on statutory, constitutional, and conceptual approaches. Primary legal materials include the 1945 Constitution, laws governing the legislature, Constitutional Court decisions, and relevant scholarly literature on bicameralism and constitutional governance. The findings reveal that the asymmetrical distribution of authority has reinforced executive dominance through legislative processes primarily controlled by the DPR, while the DPD’s participation remains consultative rather than determinative. Consequently, regional aspirations are often insufficiently reflected in national policymaking, reducing the effectiveness of checks and balances envisioned in a bicameral legislature. The study further argues that the constitutional relationship between the President and the DPD requires institutional strengthening through expanded legislative participation, more effective oversight mechanisms, and greater involvement in decision-making concerning regional autonomy, fiscal decentralization, and natural resource governance. Such reforms would enhance democratic accountability, improve the representation of regional interests, and promote a more balanced constitutional system without undermining governmental stability. Ultimately, strengthening the DPD’s constitutional position would contribute to a more effective bicameral legislature capable of supporting responsive governance and reinforcing Indonesia’s constitutional democracy.